Analisis Dampak Harga Minyak Dunia dan Nilai Tukar Terhadap Pertumbuhan Ekonomi Indonesia Tahun 2009-2023 - Sondang Engelina Situmorang; Barika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study will look at how variations in world oil prices and currency exchange rates affect Indonesia's economic growth in the short and long term, from 2009 to 2023. Using a quantitative method using the error correction (ECM) model, the results of the study show that oil prices and exchange rates have a significant influence on Indonesia's economic growth in the long term. But on the other hand, in the short term, oil prices and exchange rates do not have a significant impact on economic growth. This research can conclude that changes in oil prices and exchange rate fluctuations have a greater impact on the long-term economy, which means that it has a very important impact on Indonesia's economic policy.